2019
DOI: 10.32598/jpr.8.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Exposure to Ambient Particulate Matter and Childhood Obesity: A Systematic Review and Meta-analysis

Abstract: Context: Physical environment contamination and in particular, air pollution might cause long-term adverse effects in child growth and a higher risk of catching non-communicable diseases later in life. Objective: This study aimed to overview the human studies on the association of exposure to ambient Particulate Matter (PM) with childhood obesity. Data Sources: We systematically searched human studies published until March 2018 in PubMed, Scopus, Ovid, ISI Web of Science, Cochrane library, and Google Scholar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Among the seven included studies, three reported on the impact of air pollutants on obesity among children and adolescents [ 23 , 35 , 36 ]. One study focused on the relationship between air pollutants and obesity among adults [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the seven included studies, three reported on the impact of air pollutants on obesity among children and adolescents [ 23 , 35 , 36 ]. One study focused on the relationship between air pollutants and obesity among adults [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, according to the classification of epidemiological credibility, only two meta-analyses could be considered as the “recommended” epidemiological credibility of the association between air pollution and obesity [ 22 , 35 ]. Another three meta-analyses were classified as having ‘weak evidence’ [ 21 , 23 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 51 A systemic review and meta-analysis study has also shown exposure to ambient PM to be positively associated with childhood obesity. 52 Another study showed that high levels of PM 2.5 were shown to have a minor effect on obesity and contributed to an increase in the prevalence of type 2 diabetes in the United States of America. 43 Although studies have shown an association between PM and obesity, the causation remains unclear.…”
Section: Discussionmentioning
confidence: 99%